Large-particle emulsion type binder and preparation method thereof, battery diaphragm and lithium ion battery

By using a three-layer cladding structure of large-grain emulsion type binder, the lithium-ion battery separator is modified, and the problem of polyolefin separator shrinkage and melting at high temperature is solved, the stability and life of the battery is improved, and the battery is improved. overall performance.

CN119119925AInactive Publication Date: 2024-12-13CYG NEW ENERGY MATERIAL RESEARCH INSTITUTE (GUANGDONG) CO LTD

Patent Information

Application Number
CN202411589198.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The polyolefin separators of lithium-ion batteries are prone to shrink and melt under high temperature environments, resulting in short-circuit contact between positive and negative electrodes and reducing battery life.

Method used

A large-grain emulsion type binder is used, which comprises a three-layer coated structure, from the inside to the outside, and a microsphere seed, core layer and shell layer are successively prepared by combining a specific monomer and an initiator. and highly ionic conductivity binder used to modify battery separators.

Benefits of technology

It improves the stability and mechanical properties of the battery separator, extends the service life of the battery, and improves the overall battery performance and cycle life by improving the interface stability of the electrode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119925A_ABST
    Figure CN119119925A_ABST
Patent Text Reader

Abstract

The invention discloses a large-particle emulsion type binder and a preparation method thereof, a battery diaphragm and a lithium ion battery, the large-particle emulsion type binder comprises particles, D10 of the particles is greater than or equal to 1.2 [mu] m, D50 is 1.5-2.5 [mu] m, D90 is less than or equal to 4 [mu] m, D99 is less than or equal to 6 [mu] m, and the particles comprise microsphere seeds, a core layer coating the outer surface of the microsphere seeds and a shell layer coating the outer surface of the core layer. According to the large-particle emulsion type binder provided by the invention, the stability of the binder is improved through a three-layer coating structure, and the viscosity of the large-particle emulsion type binder is favorably changed through the outermost shell layer structure, so that the emulsion type binder with proper viscosity is obtained; the reactive emulsifier containing a sulfonic acid group is adopted, and the sulfonic acid group has good compatibility with Ca < 2 + >, Mg < 2 + > or other heavy metal ions, so that the ionic conductivity of the binder can be enhanced, the interface stability of the electrode material can be improved, the overall performance of the battery can be improved, and the cycle life of the battery can be prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a large-particle emulsion binder and a preparation method thereof, a battery separator and a lithium ion battery. Background Art

[0002] Normally, the battery separator of lithium-ion batteries is generally a polyolefin separator, such as polyethylene separator, polypropylene separator, etc. They have excellent mechanical properties, stable electrochemical properties and low cost advantages, so they are widely used in lithium-ion batteries. However, due to its low melting point (the melting point of polypropylene separator is only 165°C), polyolefin separators are prone to shrinkage and melting in high temperature environments, resulting in short circuits between the positive and negative electrodes. Surface treatment and modification of the substrate of the battery separator, such as with the help of a binder, can improve the safety of the separator. Summary of the invention

[0003] The main purpose of the present invention is to provide a large-particle emulsion binder and a preparation method thereof, a battery separator and a lithium-ion battery, aiming to improve the stability of the binder for the battery separator, thereby helping to increase the battery life.

[0004] To achieve the above object, the present invention provides a large-particle emulsion binder, the large-particle emulsion binder comprises particles, the particles have D10 ≥ 1.2 μm, D50 is 1.5-2.5 μm, D90 ≤ 4 μm, and D99 ≤ 6 μm, the particles comprise microsphere seeds, a core layer coated on the outer surface of the microsphere seeds, and a shell layer coated on the outer surface of the core layer, wherein: The raw materials used to prepare the microsphere seeds include a first monomer, a first initiator, a dispersant and a first solvent, wherein the first monomer includes methyl methacrylate, styrene, N-methylacetamide and hydroxyethyl methacrylate; The raw materials used to prepare the core layer include a second initiator; The raw materials used to prepare the shell layer include a second monomer, a third initiator, an emulsifier and a second solvent. The second monomer includes 2-hydroxyethyl acrylate, carboxyethyl acrylate, and ethylene glycol dimethacrylate. The emulsifier includes any one of sodium dodecyl sulfate, epoxy resin, polyvinyl pyrrolidone, and allyloxy nonylphenoxy methanol polyoxyethylene ether.

[0005] Optionally, the first initiator includes any one of azobisisobutyronitrile, sodium persulfate, potassium persulfate, and ammonium persulfate, the first solvent includes ethanol and pure water, and the dispersant includes polyvinyl pyrrolidone.

[0006] Optionally, the second initiator includes any one of azobisisobutyronitrile, sodium persulfate, potassium persulfate, and ammonium persulfate.

[0007] Optionally, the third initiator includes any one of azobisisobutyronitrile, sodium persulfate, potassium persulfate, and ammonium persulfate, and the second solvent includes pure water.

[0008] Optionally, the particles have a D10 ≥ 1.2 μm, a D50 of 1.5-2.5 μm, a D90 ≤ 4 μm, and a D99 ≤ 6 μm.

[0009] To achieve the above object, the present invention also provides a method for preparing the large-particle emulsion binder as described above, comprising the following steps: The dispersant and the first solvent are stirred and mixed, and then the first monomer is added for pre-emulsification, and then the temperature is raised to 70-73° C. and the first initiator is added, and the mixture is stirred for reaction to obtain a first emulsion; Adding a second initiator to the first emulsion, controlling the stirring speed to 180-220 rpm, and stirring the reaction to obtain a second emulsion; Mixing and stirring the second monomer, the emulsifier, and the second solvent to form a third emulsion; The second emulsion is emulsified, and then the temperature is raised to 74-78° C., and the third emulsion and the third initiator are added dropwise to the second emulsion to perform a polymerization reaction; After the polymerization reaction is completed, the temperature is lowered to no higher than 40° C., filtered, and discharged to obtain a large-particle emulsion adhesive.

[0010] Optionally, the mass fraction of the first monomer in the first emulsion is 18.5-20%; The mass fraction of the second monomer in the third emulsion is 4-6%.

[0011] Optionally, the mass fraction of the first initiator in the first emulsion is 0.2-2%, the mass fraction of the second initiator in the second emulsion is 0.1-1%, and the mass fraction of the third initiator in the third emulsion is 0.1-1%.

[0012] Furthermore, the present invention also provides a battery separator, comprising the large-particle emulsion binder as described above or the large-particle emulsion binder prepared by the preparation method of the large-particle emulsion binder as described above.

[0013] Furthermore, the present invention also provides a lithium-ion battery, which includes the battery separator as described above.

[0014] The large-particle emulsion binder provided by the present invention comprises a three-layer coating structure, which comprises a microsphere seed, a core layer and a shell layer from the inside to the outside. The three-layer coating structure improves the stability of the binder, and the outermost shell layer structure is conducive to changing the viscosity of the large-particle emulsion binder. In addition, the particle size of the particles is regulated to obtain an emulsion binder with suitable viscosity. A reactive emulsifier containing a sulfonic acid group is used, and the sulfonic acid group has a strong affinity for Ca 2+ Mg 2+ Or other heavy metal ions have good compatibility, can enhance the ionic conductivity of the binder, improve the interface stability of the electrode material, thereby helping to improve the overall performance and cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0016] Figures 1 to 3 This is a scanning electron microscope image of the large-particle emulsion type binder provided by the present invention; Figure 4 A particle size distribution diagram of the large-particle emulsion binder provided by the present invention; Figure 5 The particle size distribution diagram of the emulsion type binder prepared in the comparative example; Figure 6 The present invention is a schematic flow chart of an embodiment of a method for preparing a large-particle emulsion-type adhesive provided by the present invention.

[0017] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0018] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.

[0019] The invention provides a large-particle emulsion binder, which comprises particles, wherein D10 of the particles is ≥1.2 μm, D50 is 1.5-2.5 μm, D90 is ≤4 μm, and D99 is ≤6 μm, and the particles comprise microsphere seeds, a core layer coated on the outer surface of the microsphere seeds, and a shell layer coated on the outer surface of the core layer, wherein: raw materials for preparing the microsphere seeds comprise a first monomer, a first initiator, a dispersant, and a first solvent, wherein the first monomer comprises methyl methacrylate, styrene, N-methylacetamide, and hydroxyethyl methacrylate; raw materials for preparing the core layer comprise a second initiator; raw materials for preparing the shell layer comprise a second monomer, a third initiator, an emulsifier, and a second solvent, wherein the second monomer comprises 2-hydroxyethyl acrylate, carboxyethyl acrylate, and ethylene glycol dimethacrylate, and the emulsifier comprises any one of sodium dodecyl sulfonate, epoxy resin, polyvinyl pyrrolidone, and allyloxy nonylphenoxy methanol polyoxyethylene ether.

[0020] The particles in the large-particle emulsion type binder prepared by the present invention are in a uniformly dispersed state. The scanning electron microscope observation images of the large-particle emulsion type binder provided in some embodiments are as follows: Figure 1 , Figure 2 and Figure 3 The particle size distribution is shown in Figure 4As shown. More specifically, in some embodiments of the present invention, the D10 of the particles is ≥1.2μm, D50 is 1.5~2.5μm, D90≤4μm, and D99≤6μm. Among them, D10 refers to the equivalent diameter of the largest particle when the cumulative distribution in the particle size distribution curve is 10%, D50 refers to the equivalent diameter of the largest particle when the cumulative distribution in the particle size distribution curve is 50%, D90 refers to the equivalent diameter of the largest particle when the cumulative distribution in the particle size distribution curve is 90%, and D99 refers to the equivalent diameter of the largest particle when the cumulative distribution in the particle size distribution curve is 90%. Within this particle size distribution range, the adhesion, rheology and mechanical properties of the binder can be improved, and the small and uniform binder particles help to form a dense and flawless coating, improving the surface gloss and wear resistance of the coating.

[0021] The large-particle emulsion binder provided by the present invention comprises a three-layer coating structure, which comprises a microsphere seed, a core layer and a shell layer from the inside to the outside. The microsphere seed is prepared by styrene, N-methylacetamide, hydroxyethyl methacrylate and methyl methacrylate, and then the core layer and the shell layer are coated. The stability of the binder is improved by the three-layer coating structure, and the mechanical strength and elasticity of the binder are improved, and the swelling rate of the battery electrolyte is reduced, which is beneficial to improving the service life of the battery. The outermost shell layer structure is beneficial to changing the viscosity of the large-particle emulsion binder, and the particle size of the particles is regulated to obtain an emulsion binder with suitable viscosity. A reactive emulsifier containing a sulfonic acid group is used, and the sulfonic acid group has a strong affinity for Ca 2+ Mg 2+ Or other heavy metal ions have good compatibility, can enhance the ionic conductivity of the binder, improve the interface stability of the electrode material, thereby helping to improve the overall performance and cycle life of the battery.

[0022] In some embodiments of the present invention, the first initiator includes any one of azobisisobutyronitrile, sodium persulfate, potassium persulfate, and ammonium persulfate. Further, in some specific embodiments of the present invention, the first initiator includes azobisisobutyronitrile, which has a lower temperature for initiating the reaction than other initiators, is suitable for non-aqueous phase systems, and is suitable for the polymerization reaction of oil-soluble monomers.

[0023] In some embodiments of the present invention, the first solvent includes ethanol and pure water, which is more environmentally friendly and is conducive to saving resources. Further, in some specific embodiments of the present invention, the mass ratio of ethanol to water in the first solvent is 1:9.

[0024] In some embodiments of the present invention, the dispersant includes polyvinyl pyrrolidone, which has good solubility, film-forming property, adhesion and biocompatibility, and helps to improve the adhesion and durability of the binder coating during use of the battery.

[0025] In some embodiments of the present invention, the second initiator includes any one of azobisisobutyronitrile, sodium persulfate, potassium persulfate, and ammonium persulfate. Further, in some specific embodiments of the present invention, the second initiator includes ammonium persulfate, which has a high initiation ability for the free radical polymerization reaction of the polymerized vinyl monomer, has good solubility in water, low cost, and is environmentally friendly.

[0026] In some embodiments of the present invention, the third initiator includes any one of azobisisobutyronitrile, sodium persulfate, potassium persulfate, and ammonium persulfate. Further, in some specific embodiments of the present invention, the third initiator includes sodium persulfate, which has a high initiation ability for the free radical polymerization reaction of polymerized vinyl monomers, good solubility in water, low cost, environmentally friendly, and is more suitable for high temperature reactions than ammonium persulfate.

[0027] It should be noted that, in the present invention, the first initiator, the second initiator, and the third initiator may be the same as or different from each other, and each of them only needs to be selected from any one of azobisisobutyronitrile, sodium persulfate, potassium persulfate, and ammonium persulfate, and the specific amount can be adjusted accordingly according to the actual reaction situation.

[0028] In some embodiments of the present invention, the second solvent includes pure water, which reduces the use of organic solvents and is environmentally friendly.

[0029] The present invention also provides a method for preparing the large-particle emulsion type binder as described above. Figure 6 FIG. 1 is an example of a method for preparing a large particle emulsion type adhesive provided by the present invention. Figure 6 As shown, in this embodiment, the preparation method of the large-particle emulsion binder includes the following steps: Step S10, stirring and mixing the dispersant and the first solvent, adding the first monomer for pre-emulsification, then heating to 70-73° C. and adding the first initiator, stirring and reacting to obtain a first emulsion; Step S20, adding a second initiator to the first emulsion, controlling the stirring speed to 180-220 rpm, and stirring the reaction to obtain a second emulsion; Step S30, mixing and stirring the second monomer, the emulsifier, and the second solvent to form a third emulsion; Step S40, emulsifying the second emulsion, then heating it to 74-78° C., and then dropping the third emulsion and the third initiator into the second emulsion to perform a polymerization reaction; Step S50, after the polymerization reaction is completed, the temperature is lowered to no higher than 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0030] It should be noted that the present invention does not limit the order between step S20 and step S30, and step S20 can be performed first and step S30 can be performed later, or step S30 can be performed first and step S20 can be performed later, or step S20 and step S30 can be performed simultaneously, as long as the second emulsion and the third emulsion are prepared respectively before step S40.

[0031] The large-particle emulsion binder provided by the present invention comprises a three-layer coating structure, which comprises a microsphere seed, a core layer and a shell layer from the inside to the outside. The microsphere seed is prepared by styrene, N-methylacetamide, hydroxyethyl methacrylate and methyl methacrylate, and then the core layer and the shell layer are coated. The stability of the binder is improved by the three-layer coating structure, the mechanical strength and elasticity are improved, the swelling rate is reduced, and the service life of the battery is improved. The outermost shell layer structure is conducive to changing the viscosity of the large-particle emulsion binder, and the particle size of the particles is regulated to obtain an emulsion binder with suitable viscosity. A reactive emulsifier containing a sulfonic acid group is used, and the sulfonic acid group has a strong affinity for Ca 2+ Mg 2+ Or other heavy metal ions have good compatibility, can enhance the ion conductivity of the binder, improve the interface stability of the electrode material, and thus help improve the overall performance and cycle life of the battery. The large-particle emulsion binder provided by the present invention is prepared based on an aqueous system, which reduces the use of organic solvents, is conducive to improving the environmental protection and safety of the production process, and can simplify the manufacturing process and reduce costs.

[0032] In some embodiments of the present invention, the mass fraction of the first monomer in the first emulsion is 18.5-20%, and the mass fraction of the second monomer in the third emulsion is 4-6%. The regulation of the monomer content is conducive to controlling the polymerization rate. The appropriate monomer content can adjust the rate of the polymerization reaction to avoid excessively fast reaction leading to uneven polymerization or too slow reaction affecting production efficiency; secondly, the appropriate monomer content is conducive to regulating the viscosity of the binder so that it has good fluidity and filling capacity in subsequent applications; furthermore, regulating the monomer content is also conducive to controlling the molecular weight and distribution of the final polymer to ensure that the binder has consistent performance; in addition, the appropriate amount of monomer helps to reduce the residue of unreacted reaction, reduce potential harm to the environment and users, and improve the safety and environmental performance of the product; in addition, controlling the monomer content can also reduce the phase separation phenomenon of the finished binder during subsequent storage, and maintain the consistency and uniformity of the product.

[0033] In some embodiments of the present invention, the mass fraction of the first initiator in the first emulsion is 0.2-2%, the mass fraction of the second initiator in the second emulsion is 0.1-1%, and the mass fraction of the third initiator in the third emulsion is 0.1-1%. The higher the reaction temperature, the faster the initiator decomposition rate, so in the embodiments of the present invention, it is preferred to reduce the amount of the third initiator to avoid too rapid reaction resulting in a decrease in molecular weight or excessive chain breaks.

[0034] In some embodiments of the present invention, the mass fraction of the dispersant in the first emulsion is 0.5-2%, and the mass fraction of the emulsifier in the third emulsion is 0.5-2%.

[0035] In some embodiments of the present invention, the "pre-emulsification" described in step S10 can be achieved with the aid of a homogenizer, and the emulsification can be uniformly achieved by stirring at a certain speed for a certain time. The stirring speed is usually controlled to be 150-180 rpm, and the stirring time is about 20 minutes.

[0036] In some embodiments of the present invention, the "emulsification operation" described in step S30 refers to stirring at a certain speed for a certain time to make the emulsification uniform. Usually, the speed is controlled to be 150-180 rpm and the stirring time is about 30 minutes.

[0037] In the present invention, the purpose of controlling the rotation speed to 180-220 rpm in step S20 is to make the reaction process rotation speed uniform and prevent the generation of small nuclei due to too fast or too slow shooting. Preferably, in some embodiments of the present invention, all steps involving stirring reaction in step S10, step S30, and step S40 can control the stirring speed to be within 180-220 rpm.

[0038] In addition, in the present invention, the reaction time can be controlled according to the particle size results. Preferably, the reaction time for preparing the first emulsion by stirring the reaction after adding the first initiator in step S10 is about 6 to 10 hours, the reaction time for preparing the second emulsion by stirring the reaction after adding the second initiator in step S20 is about 50 to 70 minutes, and the reaction time for preparing the third emulsion in step S30 is about 6 to 8 hours.

[0039] Furthermore, the present invention also provides a battery separator, comprising the large-particle emulsion binder as described above or the large-particle emulsion binder prepared by the method for preparing the large-particle emulsion binder as described above. It should be noted that the battery separator provided by the present invention has all the beneficial effects of the large-particle emulsion binder, which will not be described one by one here.

[0040] Furthermore, the present invention also provides a lithium ion battery, the lithium ion battery comprising the battery separator as described above. It should be noted that the lithium ion battery provided by the present invention has all the beneficial effects of the above large particle emulsion binder, which will not be described in detail here.

[0041] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0042] Example 1: (1) The dispersant (polyvinylpyrrolidone) and the first solvent (ethanol and pure water) are stirred and mixed in a homogenizer at a speed of 160 rpm, and then the first monomer (methyl methacrylate, styrene, N-methylacetamide, hydroxyethyl methacrylate) is added and stirred for 20 minutes for pre-emulsification, and then the temperature is raised to 72°C, and the first initiator (azobisisobutyronitrile) is added, and the reaction is stirred at a speed of 200 rpm for 8 hours to obtain a first emulsion; wherein the mass fraction of the first monomer in the first emulsion is 19.1%, the mass fraction of the dispersant in the first emulsion is 1.0%, and the mass fraction of the first initiator in the first emulsion is 1.0%.

[0043] (2) Adding a second initiator (ammonium persulfate) to the prepared first emulsion, controlling the stirring speed to 180 rpm, stirring and reacting for 1 hour, to prepare a second emulsion; wherein the mass fraction of the second initiator in the second emulsion is 0.5%.

[0044] (3) The second monomer (2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate), the emulsifier (sodium dodecyl sulfate, epoxy resin, polyvinyl pyrrolidone, allyloxy nonylphenoxy methanol polyoxyethylene ether), and the second solvent (pure water) were mixed, and stirred at a speed of 200 rpm for 7 hours to obtain a third emulsion; wherein the mass fraction of the second monomer in the third emulsion was 5%, and the mass fraction of the emulsifier in the third emulsion was 0.8%.

[0045] (4) The prepared second emulsion was stirred at a rotation speed of 160 rpm for 30 min to fully emulsify it, and then the temperature was raised to 76°C. The third emulsion and the third initiator (sodium persulfate) were then added dropwise to the second emulsion to carry out a polymerization reaction; wherein the mass fraction of the third initiator in the third emulsion was 0.4%.

[0046] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0047] After testing, the particle size test results of the particles in the second emulsion prepared in step (2) are: D10=1.333μm, D50=2.121μm, D90=3.596μm, D99=5.363μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=1.425μm, D50=2.378μm, D90=3.955μm, D99=5.540μm; Meet the particle size requirements.

[0048] Example 2: (1) The dispersant (polyvinyl pyrrolidone) and the first solvent (ethanol and pure water) are stirred and mixed in a homogenizer at a speed of 160 rpm, and then the first monomer (methyl methacrylate, styrene, N-methylacetamide, hydroxyethyl methacrylate) is added and stirred for 20 minutes for pre-emulsification, and then the temperature is raised to 70°C and the first initiator (azobisisobutyronitrile) is added, and the reaction is stirred at a speed of 180 rpm for 6 hours to obtain a first emulsion; wherein the mass fraction of the first monomer in the first emulsion is 18%, the mass fraction of the dispersant in the first emulsion is 0.8%, and the mass fraction of the first initiator in the first emulsion is 0.2%.

[0049] (2) Adding a second initiator (ammonium persulfate) to the prepared first emulsion, controlling the stirring speed to 160 rpm, stirring and reacting for 1 hour, to prepare a second emulsion; wherein the mass fraction of the second initiator in the second emulsion is 0.1%.

[0050] (3) The second monomer (2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate), the emulsifier (sodium dodecyl sulfonate, epoxy resin, polyvinyl pyrrolidone, allyloxy nonylphenoxy methanol polyoxyethylene ether), and the second solvent (pure water) were mixed, and then stirred at a speed of 180 rpm for 6 hours to obtain a third emulsion; wherein the mass fraction of the second monomer in the third emulsion is 4%, and the mass fraction of the emulsifier in the third emulsion is 0.5%.

[0051] (4) The prepared second emulsion was stirred at a rotation speed of 150 rpm for 30 min to fully emulsify it, and then the temperature was raised to 74°C. The third emulsion and the third initiator (sodium persulfate) were then added dropwise to the second emulsion to carry out a polymerization reaction; wherein the mass fraction of the third initiator in the third emulsion was 0.1%.

[0052] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0053] After testing, the particle size test results of the particles in the second emulsion prepared in step (2) are: D10=1.328μm, D50=1.567μm, D90=3.659μm, D99=5.833μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=1.462μm, D50=2.358μm, D90=3.586μm, D99=5.957μm; Meet the particle size requirements.

[0054] Example 3: (1) The dispersant (polyvinylpyrrolidone) and the first solvent (ethanol and pure water) are stirred and mixed in a homogenizer at a speed of 150 rpm, and then the first monomer (methyl methacrylate, styrene, N-methylacetamide, hydroxyethyl methacrylate) is added and stirred for 20 minutes for pre-emulsification, and then the temperature is raised to 72°C, and the first initiator (azobisisobutyronitrile) is added, and the reaction is stirred at a speed of 170 rpm for 7 hours to obtain a first emulsion; wherein the mass fraction of the first monomer in the first emulsion is 18.5%, the mass fraction of the dispersant in the first emulsion is 0.5%, and the mass fraction of the first initiator in the first emulsion is 0.5%.

[0055] (2) Adding a second initiator (ammonium persulfate) to the prepared first emulsion, controlling the stirring speed to 170 rpm, stirring and reacting for 50 min, to prepare a second emulsion; wherein the mass fraction of the second initiator in the second emulsion is 0.3%.

[0056] (3) The second monomer (2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate), the emulsifier (sodium dodecyl sulfate, epoxy resin, polyvinyl pyrrolidone, allyloxy nonylphenoxy methanol polyoxyethylene ether), and the second solvent (pure water) were mixed, and stirred at a speed of 190 rpm for 8 hours to obtain a third emulsion; wherein the mass fraction of the second monomer in the third emulsion was 4.5%, and the mass fraction of the emulsifier in the third emulsion was 0.6%.

[0057] (4) The prepared second emulsion was stirred at a rotation speed of 170 rpm for 30 min to fully emulsify it, and then the temperature was raised to 75° C. The third emulsion and the third initiator (sodium persulfate) were added dropwise to the second emulsion to carry out a polymerization reaction; wherein the mass fraction of the third initiator in the third emulsion was 0.2%.

[0058] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0059] After testing, the particle size test results of the particles in the second emulsion prepared in step (2) are: D10=1.293μm, D50=2.205μm, D90=3.613μm, D99=5.286μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=1.489μm, D50=2.427μm, D90=3.973μm, D99=5.604μm; Meet the particle size requirements.

[0060] Example 4: (1) The dispersant (polyvinyl pyrrolidone) and the first solvent (ethanol and pure water) are stirred and mixed in a homogenizer at a speed of 170 rpm, and then the first monomer (methyl methacrylate, styrene, N-methylacetamide, hydroxyethyl methacrylate) is added and stirred for 20 minutes for pre-emulsification, and then the temperature is raised to 72.5°C, and the first initiator (azobisisobutyronitrile) is added, and the reaction is stirred at a speed of 210 rpm for 9 hours to obtain a first emulsion; wherein the mass fraction of the first monomer in the first emulsion is 19.5%, the mass fraction of the dispersant in the first emulsion is 1.5%, and the mass fraction of the first initiator in the first emulsion is 1.5%.

[0061] (2) Adding a second initiator (ammonium persulfate) to the prepared first emulsion, controlling the stirring speed to 190 rpm, stirring and reacting for 70 minutes, to prepare a second emulsion; wherein the mass fraction of the second initiator in the second emulsion is 0.8%.

[0062] (3) The second monomer (2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate), the emulsifier (sodium dodecyl sulfate, epoxy resin, polyvinyl pyrrolidone, allyloxy nonylphenoxy methanol polyoxyethylene ether), and the second solvent (pure water) were mixed, and stirred at a speed of 210 rpm for 6.5 hours to obtain a third emulsion; wherein the mass fraction of the second monomer in the third emulsion was 5.5%, and the mass fraction of the emulsifier in the third emulsion was 1.0%.

[0063] (4) The prepared second emulsion was stirred at a rotation speed of 180 rpm for 30 min to fully emulsify it, and then the temperature was raised to 77°C. The third emulsion and the third initiator (sodium persulfate) were then added dropwise to the second emulsion to carry out a polymerization reaction; wherein the mass fraction of the third initiator in the third emulsion was 0.6%.

[0064] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0065] After testing, the particle size test results of the particles in the second emulsion prepared in step (2) are: D10=1.396μm, D50=2.205μm, D90=3.642μm, D99=5.487μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=1.528μm, D50=2.439μm, D90=3.992μm, D99=5.597μm; Meet the particle size requirements.

[0066] Example 5: (1) The dispersant (polyvinyl pyrrolidone) and the first solvent (ethanol and pure water) are stirred and mixed at a speed of 180 rpm in a homogenizing mixer, and then the first monomer (methyl methacrylate, styrene, N-methylacetamide, hydroxyethyl methacrylate) is added and the stirring is continued for 20 minutes for pre-emulsification, and then the temperature is raised to 73°C, and the first initiator (azobisisobutyronitrile) is added and stirred at a speed of 220 rpm for 10 hours to obtain a first emulsion; wherein the mass fraction of the first monomer in the first emulsion is 20%, the mass fraction of the dispersant in the first emulsion is 2.0%, and the mass fraction of the first initiator in the first emulsion is 2.0%.

[0067] (2) Adding a second initiator (ammonium persulfate) to the prepared first emulsion, controlling the stirring speed to 200 rpm, stirring and reacting for 1 hour, to prepare a second emulsion; wherein the mass fraction of the second initiator in the second emulsion is 1.0%.

[0068] (3) The second monomer (2-hydroxyethyl acrylate, carboxyethyl acrylate, ethylene glycol dimethacrylate), the emulsifier (sodium dodecyl sulfate, epoxy resin, polyvinyl pyrrolidone, allyloxy nonylphenoxy methanol polyoxyethylene ether), and the second solvent (pure water) were mixed, and the mixture was stirred at a speed of 220 rpm for 7.5 h to obtain a third emulsion; wherein the mass fraction of the second monomer in the third emulsion was 6%, and the mass fraction of the emulsifier in the third emulsion was 0.9%.

[0069] (4) The prepared second emulsion was stirred at a rotation speed of 165 rpm for 30 min to fully emulsify it, and then the temperature was raised to 78°C. The third emulsion and the third initiator (sodium persulfate) were then added dropwise to the second emulsion to carry out a polymerization reaction; wherein the mass fraction of the third initiator in the third emulsion was 1.0%.

[0070] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0071] After testing, the particle size test results of the particles in the second emulsion prepared in step (2) are: D10=1.340μm, D50=2.326μm, D90=3.703μm, D99=5.512μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=1.531μm, D50=2.446μm, D90=3.899μm, D99=5.664μm; Meet the particle size requirements.

[0072] Comparative Example 1: (1) The dispersant (polyacrylamide) and the solvent (methanol and pure water) were stirred and mixed in a homogenizer at a speed of 160 rpm, and then the monomers (methyl acrylate, styrene, N-methylacetamide, hydroxyethyl methacrylate) were added and stirred for 20 min for pre-emulsification, and then the temperature was raised to 72°C, and the initiator (ammonium persulfate) was added and stirred for 8 h at a speed of 180 rpm to obtain an emulsion; wherein the mass fraction of the monomer in the emulsion was 19.1%, the mass fraction of the dispersant in the emulsion was 1.0%, and the mass fraction of the initiator in the emulsion was 1%.

[0073] (2) adding an initiator (ammonium persulfate) to the obtained emulsion, controlling the stirring speed to 180 rpm, stirring and reacting for 1 hour to obtain a core layer emulsion; wherein the mass fraction of the initiator in the core layer emulsion is 0.5%.

[0074] (3) Mixing monomers (acrylic acid, carboxymethyl acrylamide, maleic anhydride), emulsifier (octylphenol polyoxyethylene ether), and solvent (methanol and pure water), stirring and reacting at a speed of 200 rpm for 7 hours, and preparing a shell emulsion; wherein the mass fraction of the monomer in the shell emulsion is 5%, and the mass fraction of the emulsifier in the shell emulsion is 0.8%.

[0075] (4) The core layer emulsion was stirred at 160 rpm for 30 min to fully emulsify it, and then the temperature was raised to 76°C. The shell layer emulsion and initiator (ammonium persulfate) were then added dropwise to the core layer emulsion to carry out a polymerization reaction. The mass fraction of the initiator in the shell layer emulsion was 0.5%.

[0076] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0077] After testing, the particle size test results of the particles in the core layer emulsion prepared in step (2) are: D10=1.173μm, D50=1.538μm, D90=2.017μm, D99=2.245μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=1.315μm, D50=1.744μm, D90=2.322μm, D99=2.732μm; The particle size does not meet the requirements.

[0078] Comparative Example 2: (1) The dispersant (polyacrylamide) and the solvent (methanol and pure water) were stirred and mixed in a homogenizer at a speed of 160 rpm, and then the monomers (styrene, ethyl acrylate, N-methylacetamide, hydroxyethyl methacrylate) were added and stirred for 20 min for pre-emulsification, and then the temperature was raised to 72°C, and the initiator (ammonium persulfate) was added and stirred at a speed of 180 rpm for 8 h to obtain an emulsion; wherein the mass fraction of the monomer in the solution was 19.1%, the mass fraction of the dispersant in the emulsion was 1.0%, and the mass fraction of the initiator in the emulsion was 1%.

[0079] (2) adding an initiator (ammonium persulfate) to the obtained emulsion, controlling the stirring speed to 180 rpm, stirring and reacting for 1 hour to obtain a core layer emulsion; wherein the mass fraction of the initiator in the core layer emulsion is 0.5%.

[0080] (3) Mixing monomers (acrylic acid, carboxymethyl acrylamide, maleic anhydride), emulsifier (octylphenol polyoxyethylene ether), and solvent (methanol and pure water), stirring and reacting at a speed of 200 rpm for 7 hours, and preparing a shell emulsion; wherein the mass fraction of the monomer in the shell emulsion is 5%, and the mass fraction of the emulsifier in the shell emulsion is 0.8%.

[0081] (4) The core layer emulsion was stirred at 160 rpm for 30 min to fully emulsify it, and then the temperature was raised to 76°C. The shell layer emulsion and initiator (ammonium persulfate) were then added dropwise to the core layer emulsion to carry out a polymerization reaction. The mass fraction of the initiator in the shell layer emulsion was 0.5%.

[0082] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0083] After testing, the particle size test results of the particles in the core layer emulsion prepared in step (2) are: D10=1.136μm, D50=1.533μm, D90=2.064μm, D99=2.606μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=1.176μm, D50=1.608μm, D90=2.151μm, D99=2.692μm; The particle size does not meet the requirements, and there is filter residue on the post-processing filter cloth.

[0084] Comparative Example 3: (1) The dispersant (polyacrylamide) and the solvent (methanol and pure water) were stirred and mixed in a homogenizer at a speed of 160 rpm, and then the monomers (methyl styrene, octyl acrylate, N-methylacetamide, hydroxyethyl methacrylate) were added and stirred for 20 min for pre-emulsification, and then the temperature was raised to 72°C, and the initiator (ammonium persulfate) was added and stirred at a speed of 180 rpm for 8 h to obtain an emulsion; wherein the mass fraction of the monomer in the solution was 19.1%, the mass fraction of the dispersant in the emulsion was 1.0%, and the mass fraction of the initiator in the emulsion was 1%.

[0085] (2) adding an initiator (ammonium persulfate) to the obtained emulsion, controlling the stirring speed to 180 rpm, stirring and reacting for 1 hour to obtain a core layer emulsion; wherein the mass fraction of the initiator in the core layer emulsion is 0.5%.

[0086] (3) Mixing monomers (acrylic acid, carboxymethyl acrylamide, maleic anhydride), emulsifier (polyoxyethylene lauryl alcohol ether), and solvent (methanol and pure water), stirring at 200 rpm for 7 h, and preparing a shell emulsion; wherein the mass fraction of the monomer in the shell emulsion is 5%, and the mass fraction of the emulsifier in the shell emulsion is 0.8%.

[0087] (4) The core layer emulsion was stirred at 160 rpm for 30 min to fully emulsify it, and then the temperature was raised to 76°C. The shell layer emulsion and initiator (ammonium persulfate) were then added dropwise to the core layer emulsion to carry out a polymerization reaction. The mass fraction of the initiator in the shell layer emulsion was 0.5%.

[0088] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0089] After testing, the particle size test results of the particles in the second emulsion prepared in step (2) are: D10=1.173μm, D50=1.538μm, D90=2.017μm, D99=2.245μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=1.386μm, D50=2.279μm, D90=4.436μm, D99=6.856μm; The particle size does not meet the requirements, and there is filter residue on the post-processing filter cloth.

[0090] Comparative Example 4: (1) The dispersant (polyacrylamide) and the solvent (ethanol and pure water) were stirred and mixed in a homogenizer at a speed of 160 rpm, and then the monomers (methyl styrene, methyl acrylate, N-methylacetamide, hydroxyethyl methacrylate) were added and stirred for 20 min for pre-emulsification, and then the temperature was raised to 72°C, and the initiator (sodium persulfate) was added and stirred at a speed of 180 rpm for 8 h to obtain an emulsion; wherein the mass fraction of the monomer in the solution was 19.1%, the mass fraction of the dispersant in the emulsion was 1.0%, and the mass fraction of the initiator in the emulsion was 1%.

[0091] (2) adding an initiator (sodium persulfate) to the obtained emulsion, controlling the stirring speed to 180 rpm, stirring and reacting for 1 hour to obtain a core layer emulsion; wherein the mass fraction of the initiator in the core layer emulsion is 0.5%.

[0092] (3) Mixing monomers (vinyl acetic acid, methacrylic acid, fumaric acid, hydroxymethyl acrylamide), emulsifier (polyoxyethylene lauryl alcohol ether), and solvent (ethanol and pure water), stirring at 200 rpm for 7 h to prepare a shell emulsion; wherein the mass fraction of the monomer in the shell emulsion is 5%, and the mass fraction of the emulsifier in the shell emulsion is 0.8%.

[0093] (4) The prepared core layer emulsion was stirred at a rotation speed of 160 rpm for 30 min to fully emulsify it, and then the temperature was raised to 76°C. The shell layer emulsion and initiator (sodium persulfate) were then added dropwise to the core layer emulsion to carry out a polymerization reaction; wherein the mass fraction of the initiator in the shell layer emulsion was 0.5%.

[0094] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0095] After testing, the particle size test results of the particles in the core layer emulsion prepared in step (2) are: D10=1.296μm, D50=1.724μm, D90=2.291μm, D99=2.728μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=1.396μm, D50=1.831μm, D90=2.430μm, D99=2.728μm; The particle size does not meet the requirements, and although the filter residue on the post-processing filter cloth is reduced, there is still filter residue.

[0096] Comparative Example 5: (1) The dispersant (polyvinyl pyrrolidone) and the solvent (ethanol and pure water) were stirred and mixed in a homogenizer at a speed of 160 rpm, and then monomers (methyl styrene, methyl acrylate, acrylamide, acrylonitrile, N-methylacetamide, hydroxyethyl methacrylate) were added and stirred for 20 minutes for pre-emulsification, and an initiator (sodium persulfate) was added and stirred for 8 hours at a speed of 180 rpm to obtain an emulsion; wherein the mass fraction of the monomer in the solution was 19.1%, the mass fraction of the dispersant in the emulsion was 1.0%, and the mass fraction of the initiator in the emulsion was 1%.

[0097] (2) adding an initiator (sodium persulfate) to the obtained emulsion, controlling the stirring speed to 180 rpm, stirring and reacting for 1 hour to obtain a core layer emulsion; wherein the mass fraction of the initiator in the core layer emulsion is 0.5%.

[0098] (3) Mix monomers (vinyl acetic acid, methacrylic acid, fumaric acid, carboxymethyl acrylamide), emulsifier (polyoxyethylene lauryl alcohol ether), and solvent (ethanol and pure water), and stir at 200 rpm for 7 h to prepare a shell emulsion; wherein the mass fraction of the monomer in the shell emulsion is 5%, and the mass fraction of the emulsifier in the shell emulsion is 0.8%.

[0099] (4) The prepared core layer emulsion was stirred at a rotation speed of 160 rpm for 30 min to fully emulsify it, and then the temperature was raised to 76°C. The shell layer emulsion and initiator (sodium persulfate) were then added dropwise to the core layer emulsion to carry out a polymerization reaction; wherein the mass fraction of the initiator in the shell layer emulsion was 0.5%.

[0100] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0101] After testing, the particle size test results of the particles in the core layer emulsion prepared in step (2) are: D10=1.763μm, D50=2.322μm, D90=3.081μm, D99=3.479μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=1.983μm, D50=3.213μm, D90=4.611μm, D99=5.555μm; The particle size does not meet the requirements, and small particles are released from the nucleus.

[0102] Comparative Example 6: (1) The dispersant (polyvinyl pyrrolidone) and the solvent (ethanol and pure water) were stirred and mixed in a homogenizer at a speed of 160 rpm, and then monomers (methyl acrylate, styrene, acrylamide, acrylonitrile, N-methylacetamide, hydroxyethyl methacrylate) were added and stirred for 20 minutes for pre-emulsification, and an initiator (sodium persulfate) was added and stirred for 8 hours at a speed of 180 rpm to obtain an emulsion; wherein the mass fraction of the monomer in the solution was 19.1%, the mass fraction of the dispersant in the emulsion was 1.0%, and the mass fraction of the initiator in the emulsion was 1%.

[0103] (2) adding an initiator (sodium persulfate) to the obtained emulsion, controlling the stirring speed to 180 rpm, stirring and reacting for 1 hour to obtain a core layer emulsion; wherein the mass fraction of the initiator in the core layer emulsion is 0.5%.

[0104] (3) Mix monomers (vinyl acetic acid, 2-hydroxyethyl acrylate, carboxymethyl acrylamide), emulsifier (polyoxyethylene lauryl alcohol ether), and solvent (ethanol and pure water), and stir at 200 rpm for 7 h to prepare a shell emulsion; wherein the mass fraction of the monomer in the shell emulsion is 5%, and the mass fraction of the emulsifier in the shell emulsion is 0.8%.

[0105] (4) The prepared core layer emulsion was stirred at a rotation speed of 160 rpm for 30 min to fully emulsify it, and then the temperature was raised to 76°C. The shell layer emulsion and initiator (sodium persulfate) were then added dropwise to the core layer emulsion to carry out a polymerization reaction; wherein the mass fraction of the initiator in the shell layer emulsion was 0.5%.

[0106] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0107] After testing, the particle size test results of the particles in the core layer emulsion prepared in step (2) are: D10=1.763μm, D50=2.332μm, D90=3.085μm, D99=3.459μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=2.268μm, D50=3.285μm, D90=4.458μm, D99=5.538μm; The particle size does not meet the requirements, and the particle size graph has tailing (see Figure 5 ), indicating that the particles in the prepared emulsion adhesive are sticky.

[0108] Comparative Example 7: (1) The dispersant (polyvinyl pyrrolidone) and the solvent (ethanol and pure water) were stirred and mixed in a homogenizer at a speed of 160 rpm, and then monomers (styrene, methyl methacrylate, acrylamide, acrylonitrile, N-methylacetamide, hydroxyethyl methacrylate) were added and stirred for 20 minutes for pre-emulsification, and an initiator (azobisisobutyronitrile) was added and stirred at a speed of 180 rpm for 8 hours to obtain an emulsion; wherein the mass fraction of the monomer in the solution was 19.1%, the mass fraction of the dispersant in the emulsion was 1.0%, and the mass fraction of the initiator in the emulsion was 1%.

[0109] (2) adding an initiator (azobisisobutyronitrile) to the obtained emulsion, controlling the stirring speed to 180 rpm, stirring and reacting for 1 hour to obtain a core layer emulsion; wherein the mass fraction of the initiator in the core layer emulsion is 0.5%.

[0110] (3) Mix monomers (vinyl acetic acid, 2-2-hydroxyethyl acrylate, carboxymethyl acrylamide), emulsifier (polyoxyethylene lauryl alcohol ether), and solvent (ethanol and pure water), and stir at 200 rpm for 7 h to prepare a shell emulsion; wherein the mass fraction of the monomer in the shell emulsion is 5%, and the mass fraction of the emulsifier in the shell emulsion is 0.8%.

[0111] (4) The prepared core layer emulsion was stirred at a rotation speed of 160 rpm for 30 min to fully emulsify it, and then the temperature was raised to 76°C. The shell layer emulsion and initiator (azobisisobutyronitrile) were then added dropwise to the core layer emulsion to carry out a polymerization reaction; wherein the mass fraction of the initiator in the shell layer emulsion was 0.5%.

[0112] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0113] After testing, the particle size test results of the particles in the core layer emulsion prepared in step (2) are: D10=1.983μm, D50=2.763μm, D90=4.159μm, D99=5.428μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=2.052μm, D50=2.873μm, D90=4.141μm, D99=5.374μm; The particle size does not meet the requirements.

[0114] Comparative Example 8: (1) The dispersant (polyvinyl pyrrolidone) and the solvent (ethanol and pure water) were stirred and mixed in a homogenizer at a speed of 160 rpm, and then the monomers (styrene, methyl methacrylate, N-methylacetamide, hydroxyethyl methacrylate) were added and the stirring was continued for 20 minutes for pre-emulsification, and then the initiator (azobisisobutyronitrile) was added and stirred at a speed of 180 rpm for 8 hours to obtain an emulsion; wherein the mass fraction of the monomer in the solution was 19.1%, the mass fraction of the dispersant in the emulsion was 1.0%, and the mass fraction of the initiator in the emulsion was 1%.

[0115] (2) Adding an initiator (azobisisobutyronitrile) to the prepared emulsion, and controlling the stirring speed to 180 rpm, stirring and reacting for 1 hour to obtain a core layer emulsion; wherein the amount of the initiator added is 0.5% by mass in the core layer emulsion.

[0116] (3) Mixing monomers (vinyl acetic acid, 2-2-hydroxyethyl acrylate, carboxymethyl acrylamide), emulsifiers (sodium dodecyl sulfonate, epoxy resin), and solvents (ethanol and pure water), stirring and reacting at a speed of 200 rpm for 7 hours, and preparing a shell emulsion; wherein the mass fraction of the monomer in the shell emulsion is 5%, and the mass fraction of the emulsifier in the third emulsion is 0.8%.

[0117] (4) The prepared core layer emulsion was stirred at a rotation speed of 160 rpm for 30 min to fully emulsify it, and then the temperature was raised to 76°C. The shell layer emulsion and initiator (sodium persulfate) were then added dropwise to the core layer emulsion to carry out a polymerization reaction; wherein the mass fraction of the initiator in the shell layer emulsion was 0.5%.

[0118] (5) After the polymerization reaction is completed, the temperature is lowered to 40°C, filtered, and discharged to obtain a large-particle emulsion adhesive.

[0119] After testing, the particle size test results of the particles in the core layer emulsion prepared in step (2) are: D10=1.304μm, D50=2.267μm, D90=4.096μm, D99=5.483μm; The particle size test results of the particles in the large-particle emulsion adhesive prepared in step (5) are: D10=1.225μm, D50=2.486μm, D90=4.063μm, D99=5.200μm; The particle size does not meet the requirements.

[0120] Comparative Example 9: Emulsion-type adhesive prepared according to the patent publication CN115216255A “An emulsion-type adhesive, a method for preparing an emulsion-type adhesive, and a separator”.

[0121] Its D50 is 0.8~20μm, and D90 / D10<2.

[0122] The viscosity of the emulsion-type adhesive prepared in Examples 1-5 of the present invention and Comparative Example 9 was tested respectively, and the above-mentioned adhesive was used to prepare a battery separator, and the peel strength of the battery separator was tested. The above-mentioned battery separator was matched with a pole piece, an electrolyte, etc. to prepare a lithium-ion battery, and the swelling rate of the electrolyte, the lithium ion conductivity of the battery separator, and the cycle performance of the lithium-ion battery were tested. The specific test methods and results are as follows: (1) Viscosity test A digital viscometer is used to calculate the viscosity of the liquid by measuring the torque of the rotor, using the resistance encountered by the rotating rotor when rotating in the liquid.

[0123] (2) Peel strength test Using a computerized tensile and compressive testing machine, the product adhesive is made into an electrode and coated on the copper foil. It is then dried and cut into a certain length and width, and then fixed on a glass plate. The other side is fixed on the fixture of the testing machine. The testing machine is started and tension is slowly applied. The peeling force is displayed on the system.

[0124] (3) Electrolyte swelling rate test To prepare a certain amount of dry binder sample, it is usually necessary to pre-dry it in a vacuum drying oven to constant weight to remove moisture and other volatile substances, and record the initial mass; soak the dry binder sample in a pre-selected electrolyte and soak it at room temperature for a certain period of time; take out the sample from the electrolyte, gently wipe the surface to remove the unabsorbed electrolyte, and record the mass; subsequently calculate and measure the swelling rate.

[0125] (4) Lithium ion conductivity test of battery separator A Li / battery separator / Li symmetrical battery was formed with a metal lithium sheet and the prepared battery separator. Then, an EIS analysis was performed under the conditions of a voltage of 5mV and a frequency of 0.03-500KHz to obtain the bulk resistance of the battery separator, recorded as Rs. The lithium ion conductivity of the battery separator was calculated by the following formula: Lithium ion conductivity C = T / Rs×A Where: T is the thickness of the battery separator, A is the area of ​​the battery separator.

[0126] (5) Cycle performance test of lithium-ion batteries Take the assembled lithium-ion battery, charge it at a constant current of 0.1C to the charging cut-off voltage at a temperature below 70°C, then charge it at a constant voltage until the current drops to 0.05C, let it stand for 5 minutes, then discharge it at a constant current of 0.1C to the discharge cut-off voltage, let it stand for 5 minutes, and then repeat the above constant current charging, constant voltage charging, and constant current discharging steps for 500 cycles. Among them, the charging cut-off voltage of the embodiment and the comparative example is 3.75V, and the discharge cut-off voltage is 2.5V.

[0127] The capacity retention rate (%) of a lithium-ion battery after N cycles = the discharge capacity of the Nth cycle / the discharge capacity of the first cycle × 100%.

[0128] The test results of viscosity, peel strength and swelling rate are shown in Table 1 below, and the test results of lithium ion conductivity and battery cycle performance are shown in Table 2 below.

[0129]

[0130]

[0131] It can be seen from the test results in Table 1 and Table 2 that, compared with the binder prepared in the comparative example, the large-particle emulsion binder prepared in the embodiment of the present invention has a more suitable viscosity, is more conducive to good fluidity and filling performance in the subsequent processing process, and reduces the swelling rate of the electrolyte, improves the lithium ion conductivity, is conducive to improving the service life of the battery, and also improves the cycle performance of the lithium ion battery.

[0132] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A large particle emulsion type adhesive, characterized in that: The large-particle emulsion binder comprises particles, wherein D10 of the particles is ≥1.2 μm, D50 is 1.5-2.5 μm, D90 is ≤4 μm, and D99 is ≤6 μm. The particles comprise microsphere seeds, a core layer coated on the outer surface of the microsphere seeds, and a shell layer coated on the outer surface of the core layer, wherein: The raw materials used to prepare the microsphere seeds include a first monomer, a first initiator, a dispersant and a first solvent, wherein the first monomer includes methyl methacrylate, styrene, N-methylacetamide and hydroxyethyl methacrylate; The raw materials used to prepare the core layer include a second initiator; The raw materials used to prepare the shell layer include a second monomer, a third initiator, an emulsifier and a second solvent. The second monomer includes 2-hydroxyethyl acrylate, carboxyethyl acrylate, and ethylene glycol dimethacrylate. The emulsifier includes any one of sodium dodecyl sulfate, epoxy resin, polyvinyl pyrrolidone, and allyloxy nonylphenoxy methanol polyoxyethylene ether.

2. The large-particle emulsion adhesive according to claim 1, characterized in that: The first initiator includes any one of azobisisobutyronitrile, sodium persulfate, potassium persulfate, and ammonium persulfate; the first solvent includes ethanol and pure water; and the dispersant includes polyvinyl pyrrolidone.

3. The large-particle emulsion adhesive according to claim 1, characterized in that: The second initiator includes any one of azobisisobutyronitrile, sodium persulfate, potassium persulfate, and ammonium persulfate.

4. The large-particle emulsion adhesive according to claim 1, characterized in that: The third initiator includes any one of azobisisobutyronitrile, sodium persulfate, potassium persulfate, and ammonium persulfate, and the second solvent includes pure water.

5. A method for preparing a large-particle emulsion adhesive according to any one of claims 1 to 4, characterized in that: The following steps are involved: The dispersant and the first solvent are stirred and mixed, and then the first monomer is added for pre-emulsification, and then the temperature is raised to 70-73° C. and the first initiator is added, and the mixture is stirred for reaction to obtain a first emulsion; Adding a second initiator to the first emulsion, controlling the stirring speed to 180-220 rpm, and stirring the reaction to obtain a second emulsion; Mixing and stirring the second monomer, the emulsifier, and the second solvent to form a third emulsion; Emulsifying the second emulsion, then heating it to 74-78° C., and then dropping the third emulsion and the third initiator into the second emulsion to perform a polymerization reaction; After the polymerization reaction is completed, the temperature is lowered to no higher than 40° C., filtered, and discharged to obtain a large-particle emulsion adhesive.

6. The method for preparing a large-particle emulsion-type adhesive according to claim 5, characterized in that: The mass fraction of the first monomer in the first emulsion is 18.5-20%; The mass fraction of the second monomer in the third emulsion is 4-6%.

7. The method for preparing a large-particle emulsion-type adhesive according to claim 5, characterized in that: The mass fraction of the first initiator in the first emulsion is 0.2-2%, the mass fraction of the second initiator in the second emulsion is 0.1-1%, and the mass fraction of the third initiator in the third emulsion is 0.1-1%.

8. A battery separator, characterized in that: The invention comprises a large-particle emulsion type adhesive as claimed in any one of claims 1 to 4 or a large-particle emulsion type adhesive prepared by the preparation method of a large-particle emulsion type adhesive as claimed in any one of claims 5 to 7.

9. A lithium ion battery, characterized in that: The lithium ion battery comprises the battery separator as claimed in claim 8.

Citation Information

Patent Citations

  • Emulsion type binder, preparation method of emulsion type binder and diaphragm

    CN115216255A

  • Lithium battery ceramic diaphragm binder, preparation method and lithium battery

    CN115851183A

  • Heat-resistant diaphragm binder as well as preparation method and application thereof

    CN116606616A

  • Core-shell type lithium-containing polyacrylic water-based adhesive, and preparation method therefor and use thereof

    WO2024207816A1

Cited By

  • Binder for lithium ion battery and preparation method of binder

    CN119351001A

  • Large-particle emulsion type binder and preparation method thereof, battery diaphragm and lithium ion battery

    CN120699568A